2000
DOI: 10.1088/0954-0083/12/1/316
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Novel Aromatic Polyimides from 4,4′-Diamino-4″ -Hydroxytriphenylamine and Aromatic Tetracarboxylic Dianhydrides

Abstract: Novel aromatic polyimides containing hydroxytriphenylamine units were prepared from 4,4′-diamino-4″-hydroxytriphenylamine 1 and various aromatic tetracarboxylic dianhydrides 2. The glass transition temperatures ( Tgs) of these polyimides were in the range of 274–388 °C and the 10% weight loss temperatures ( T d10s) were above 462 and 511 °C in air and nitrogen respectively. Polyimide 4f prepared from diamine 1 and 4,4′-hexafluoroisopropylidenebis(phthalic anhydride) (6FDA) was soluble not only in organic solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…As it was mentioned, one of the main drawbacks of polyimides is their low solubility. For instance, it has been reported that most of polyimides derived from 4,4′‐diamino‐4″‐hydroxytriphenylamine monomer were not soluble in organic solvents 24. The reported solubility of polyimides derived form 2,6‐bis(3‐ aminobenzoyl) pyridine was about 1 g/dL 25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mentioned, one of the main drawbacks of polyimides is their low solubility. For instance, it has been reported that most of polyimides derived from 4,4′‐diamino‐4″‐hydroxytriphenylamine monomer were not soluble in organic solvents 24. The reported solubility of polyimides derived form 2,6‐bis(3‐ aminobenzoyl) pyridine was about 1 g/dL 25…”
Section: Resultsmentioning
confidence: 99%
“…On the other hands, the solubility of polyimides derived from BTDA and 6FDA was higher than PMDA, NTDA, and PTDA‐derived polyimides. Presence of some flexible groups was the main reason for this behavior because of the fact that carbonyl and hexaflouroisopropylidene groups in BTDA and 6FDA respectively, have low rotational bond energy in comparison to the other polyimides, which reduced the polymer chains interaction and rigidity 15, 24, 30…”
Section: Resultsmentioning
confidence: 99%
“…Polymers containing Schiff base units in the main chain display many special properties, such as excellent mechanical strength, high thermal stability, semiconducting, good optoelectronic properties and thermotropic liquid crystalline behavior [5,6]. Hard segmented PUs show poor solubility in common organic solvents due to their rigid backbones [7,8], which limits their application and makes it difficult to process them.…”
Section: Introductionmentioning
confidence: 99%
“…Many PUs and polyureas were found to be insoluble in common organic solvents due to their rigid backbones,9, 10 thereby inhibiting their applications due to difficulty in their processing. To overcome such difficulties, polymer structure modification is necessary, wherein one can introduce asymmetric or bulky groups on the pendant polymer backbone or incorporate noncoplanar structural units on the main polymer chain 11–14. In our previous papers,15–17 Schiff‐based PUs, chalcone‐based PUs and azo‐based diol containing PUs have been prepared using 2,2′‐{ethane‐1,2‐diylbis(nitrilomethylylidene)}diphenol, 2,2′‐{hexane‐1,6‐diylbis(nitrilomethylylidene)} diphenol, 2,2′‐{1,4‐phenylenebis‐[nitrilomethylylidene]}diphenol, 2,2′‐{4,4′‐methylene di‐2‐methylphenylene‐1,1′‐bis[nitrilomethylylidene]}diphenol, 2,6‐bis(4‐hydroxy‐benzylidene)cyclohexanone, 4,4′‐[1,4‐phenylenedi‐diazene‐2,1‐diyl]bis(2‐carboxy‐phenol), and 4,4′‐[1,4‐phenylenedi‐diazene‐2,1‐diyl]bis(2‐chlorophenol) with different diisocyanates.…”
Section: Introductionmentioning
confidence: 99%